Evaluación de la Capacidad de Depuración de Microorganismos Eficaces en el Tratamiento de Aguas Residuales Domésticas, Moyobamba – 2014 - Sanchez Cabrera, Maritza Medaly (2014)
Faced with the need for effective treatment for wastewater That we produce daily and shed it to any surface source without giving it the Treatment, we find effective microorganisms as Wastewater treatment plants, this research aims to demonstrate the Efficiency of the synergism of microorganisms effective in the treatment of Wastewater for later use in agriculture. Samples of the domestic wastewater from the experimental well were sampled at 0, 15, 30 and 45 days analyzing physicochemical parameters (OD, pH, T, COD, BOD, SST, NO2, PO4, NTU) and microbiological (total coliforms and fecal coliforms). Under the conditions of the present study, the results showed differences in each Turbidity decreased by 64.29% from 98 to 35.0 Low temperature from 23.5 ° C to 22.8 ° C, the pH presented values ​​close to the Neutrality throughout the treatment from 6.3 to 6.7; Phosphates decreased in 25% from 0.6 mg / l to 0.45 mg / l; Nitrates were removed in 50% of 8 mg / l At 4 mg / l; For Total Suspended Solids the treatment presented an efficiency Of 48.72%; For dissolved oxygen values ​​of 3 mg / l were obtained at baseline and 2.5 mg / l At the end of treatment; The BOD was highly removed in 69.4% Decreasing thus from 320 mg / l to 98 mg / l and COD showed a decrease of 40.68% from 354 mg / l to 210 mg / l, Total Coliforms were removed in one 56,25%, thus decreasing from 2120 NMP / 100ml to 1000 NMP / 100ml and the Thermotolerant coliforms decreased by 52.83% from 1 200 NMP / 100ml to 525 NMP / 100ml. The present investigation concludes that, by applying effective microorganisms, Managed to obtain purified water, with a level of acceptability 72.7% according to ECA Category 3, with the exception of Dissolved Oxygen, Biochemical Oxygen Demand, Chemical Oxygen Demand; Therefore it is suitable for the irrigation of vegetables.